Is there a utility of adding skeletal imaging to 68-Ga-prostate-specific membrane antigen-PET/computed tomography in initial staging of patients with high-risk prostate cancer?. Issue 11 (November 2020) - Raju, Shobhana; Sharma, Anshul; Patel, Chetan; Sahoo, Ranjith; Das, Chandan J.; Kumar, Sanjay; Sharma, Akshima; Kumar, Rakesh
Abstract : Purpose: Both bone-scan and cross-sectional imaging are indicated in the staging of high-risk prostate cancer (PCa). However, 68Ga-prostate-specific membrane antigen (PSMA)-PET/computed tomography (CT) has proven to be an excellent tracer for detection of skeletal metastases. The aim of this study was to assess if adding skeletal imaging (with 18F-Fluoride-PET/CT) to 68-Ga-PSMA-PET/CT had any impact on high-risk PCa staging. Method: Fifty treatment-naive, histopathologically proven, high-risk (European Association of Urology) PCa patients underwent both 68-Ga-PSMA-PET/CT and 18F-Fluoride-PET/CT for staging. Results: Fluoride-PET/CT detected significantly a higher number of skeletal metastases/patient than PSMA-PET/CT (median 4.5/patient vs 3.0; Wilcoxan-signed-rank-test, P = 0.060) and there was a significantly higher proportion of only Fluoride-avid than only PSMA-avid lesions (McNemar-test P < 0.001). No significant advantage was seen in patient-wise metrics. Most lesions missed by PSMA-PET/CT were in flat bones (25/33). serum prostate specific antigen (S.PSA) showed positive correlation with both, the number of lesions [r(PSMA)-0.555 ( P = 0.006) and r(Fluoride)-0.622 ( P = 0.001)] as well as tumor to background ratio (TBR) [[r-0.706 ( P < 0.001) and 0.516 ( P = 0.010)]. Median TBR was significantly higher in PSMA-PET/CT (22.77 vs 16.30; P < 0.001). All three patients with only Fluoride-avid lesions (also not identified in bone-scan) showed biochemical response with additional therapy. Conclusion: Though, Fluoride-PET/CT detected a higher absolute number of lesions than PSMA-PET/CT, no significant advantage was seen in patient-wise metrics. Fluoride-PET/CT added second-line management in only 3/50 patients, which could have been reduced to 1/50, with more sensitive evaluation of flat bones in PSMA-PET-CT. Therefore, additional skeletal imaging is not needed with 68-Ga-PSMA-PET/CT in initial staging of high-risk PCa.